Abundance and Length-Weight Relationship of Fishes from Sungai Sepang Besar, Selangor - A Ya, N; R Singh, H (International Journal of Engineering and Technology, 2019)
This study was conducted to determine the abundance and the length-weight relationship of fishes of Sungai Sepang Besar (SSB), Selangor. A total of 832 individuals from 32 families comprising 50 species were collected from April 2014 to February 2015 by utilizing gill nets of various mesh size (1.25, 2.25, 2.50, 2.75, 3 and 4.5 inch) and long lines. The family Toxotidae was most abundant with a total of 474 individuals sampled comprising 2 species namely, Toxotes jaculatrix (n=288) and Toxotes chatareus (n=186). The Shannon-Weiner Index (2.37) and the Pielou Evennes (0.21) was low but the Margalef’s richness (7.29) was relatively high. Arius sagor, Photopectoralis bindus, Toxotes jaculatrix, Thryssa dussumieri, and Stolephorus indicus demonstrated positive allometric growth (b>3) while Plotosus lineatus and Toxotes chatareus showed negative allometric growth (b<3). Understanding abundance and the length-weight relationship of fish is important not only for species conservation and management, but also their habitat use.